Mediations in disinformation that intervenes the taking of preventive measures in the face of the COVID-19 health crisis - Flores González, Rubén (2022)
The lockdown situation has exposed citizens to a profusion of information about COVID-19, both official and unofficial, with different sources and varying degrees of reliability. Uncertainty spurs the search for information since the health of citizens depends on it. This study explores the mediation processes involved in building trust in actors linked to the COVID-19 pandemic and media consumption on the prevention measures that citizens take for their care. A representative sample of 1211 Mexican citizens was subject to the study. Among the main results is that citizens are very informed about COVID-19, engage in considerable media consumption, and have substantial institutional trust, particularly in non-governmental organizations. Regarding prevention measures, these are associated with people's trust in health sector employees. Likewise, regarding the acceptance of both true and fake news, the study showed that these are related to the preventive measures people take to mitigate the effects of the pandemic.